Intracardiac Echocardiography as a Guide for Transcatheter Closure of Patent Ductus Arteriosus. (30th July 2020) - Yoshimoto, Hironaga; Yasuto, Maeda; Inoue, Tadashi; Kagiyama, Yoshiyuki; Teramachi, Yozo; Takase, Ryuta; Koteda, Yusuke; Fukumoto, Yoshihiro; Iemura, Motofumi; Suda, Kenji
Abstract : Background . Transcatheter closure of patent ductus arteriosus (TC-PDA), conventionally guided by aortography, has become the standard treatment of this disease. The purposes of this study were to evaluate whether intracardiac echocardiography (ICE) may be used for measuring PDA size and be used as a guide for TC-PDA. Methods . This study had 2 phases. In phase 1, we compared the measurements of PDA size: pulmonary artery side diameter (PA-D), length, and aortic side diameter (Ao-D) of PDA, as measured by ICE with those measured by aortography or cardiac computed tomography (AoG/CCT) in 23 patients who underwent TC-PDA. In phase 2, we compared the demographics, fluoroscopic time, contrast volume, and complications of the TC-PDAs between 10 adult patients with ICE guidance and 16 without it. Results . In phase 1, we found great correlation and agreement between ICE and AoG/CCT in PA-D ( r = 0.985, bias −0.077 to 0.224), but moderate to poor correlation and agreement in length ( r = 0.653, bias −0.491 to 3.065) and Ao-D ( r = 0.704, bias 0.738 to 4.732), respectively. Nevertheless, all patients underwent successful TC-PDA with ICE guidance that allowed us to continuously monitor the whole process. In phase 2, TC-PDA required a significantly lower contrast volume with ICE guidance than without it, and there was no significant difference in the remaining variables between the 2 groups. Conclusion . ICE is comparable to AoG/CCT in providing accurate PA-D of the PDA and may be a safe alternative to guide TC-PDA as compared to conventional aortography.